2022
DOI: 10.1177/09544119221091346
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behavior of diamond lattice scaffolds obtained by two different design approaches with similar porosity; a numerical investigation with FEM and CFD analysis

Abstract: Scaffolds provide a suitable environment for the bone tissue to maintain its self-healing ability and help new bone-cell formation by creating structures with similar mechanical properties to the surrounding tissue. In the modeling of the scaffolds, an optimum environment is tried to be provided by changing the geometrical properties of the cell architecture such as porosity, pore size, and specific surface area. For this purpose, different design approaches have been used in studies to change these properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…258 Furthermore, recent studies have revealed the effect of various designing methods of diamond lattice on penetrability, successful cell culture, proper elastic modulus, etc. 262 Following this investigation, Timercan et al prepared lattice systems of gyroid and diamond that were mechanically exible and penetrable to liquids, thus encouraging osseointegration and decreasing complexity risks, for instance, a lack of xation, device migration, and subsidence in current intervertebral fusion devices. These structures were manufactured using Ti-6Al-4V and laser powder bed fusion.…”
Section: Fibrous Carbon Nanostructuresmentioning
confidence: 99%
“…258 Furthermore, recent studies have revealed the effect of various designing methods of diamond lattice on penetrability, successful cell culture, proper elastic modulus, etc. 262 Following this investigation, Timercan et al prepared lattice systems of gyroid and diamond that were mechanically exible and penetrable to liquids, thus encouraging osseointegration and decreasing complexity risks, for instance, a lack of xation, device migration, and subsidence in current intervertebral fusion devices. These structures were manufactured using Ti-6Al-4V and laser powder bed fusion.…”
Section: Fibrous Carbon Nanostructuresmentioning
confidence: 99%
“…Li et al [ 45 ] demonstrated that the elastic modulus is 25.9 GPa when the pore size is 0.65 mm, and 14.5 GPa when the pore size is 0.5 mm, which is comparable to the elastic modulus of adult cortical bone. Karaman et al [ 46 ] conducted compression tests on different design models with 50%, 60%, 70%, 80%, and 90% porosities and found that the structural strength decreases with increasing porosity. The mechanical properties of porous materials, like their elastic modulus and yield stress, are linked to their porosity.…”
Section: Introductionmentioning
confidence: 99%